The Comparison of Various Solution Effectivity on the Dilution of Cerumen Obturans in Vitro - Gerrard S. Dharmaratne (GoAcademica Research & Publishing, 2020)
Cerumen obturans is a pathological condition that is not life-threatening but can cause discomfort such as feeling full in the ear, pain, hearing loss and deafness as well decreased quality of life. This study aims to determine comparison of the effectiveness of six solvents, namely aquadest, NaCl salt solution 0.9%, coconut oil, olive oil, carboglycerin 10% and sodium docusate 0.5% of cerumen obturans in vitro and to know the duration the most effective contact time of a solvent against serumen solubility. This research is a laboratory experiment using 30 compacted obturated cerumen specimens weighing 40 mg each. Serumen solubility level is measured using Spectronic spectrophotometer 21. Comparison of the effectiveness of the solvent tested with using the One Way Anova test with alpha <0.05. The results show that the effectiveness of different solvents is significant at 20, 25 and 30 minutes only between Aquadest and NaCl 0.9% coconut oil and olive oil using a spectrophotometer. Tim effective contact in vitro is ≥ 20 minutes and inclined increase to the 30 minute limit. In the 20th and 25th minutes, NaCl 0.9% is the most effective solvent while at the most 30th minute effective is aquadest. Olive oil and coconut oil are solvents the lowest effectiveness. Water-based solvents are more effective than fat based solvent.